Reform of the CAP: Progress for grasslands and livestock farming? - Peeters A. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
The European Commission (EC) presented recently a proposition for a reform of the Common Agricultural Policy (CAP) after 2013. This proposal continues some of the present objectives and includes new ones that take into account the enlargement to new Member States. The mechanisms designed by the EC for reaching these objectives, especially for the \"Greening\" component of pillar 1, are though very unlikely to succeed. The definition of permanent grassland is far too restrictive and inadequate. Seminatural grasslands and High Nature Value farmland are not specifically targeted although they are the most valuable ecosystems of the farmland area. Greening measures are too general, not targeted, not contractual and based on one-year farmers\' commitments. They do not include farmers\' advice and training, and a convincing control system. Most CAP expenditures should shift from pillar 1 to pillar 2 and the agrienvironmental scheme. In the medium term, CAP expenditures should support the emergence of a market of public goods (biodiversity, landscape and carbon storage mainly) supported by pillar 2 budget (public money for public goods!). An increase of the grassland area and the implementation of an efficient system for biodiversity conservation in agriculture are highly desirable.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)